IOP Conference Series: Earth and Environmental Science - Panin specialist in the field of material science Professor of Tomsk Polytechnic University, Doctor of technical sciences; Aleksenko Specialist in the field of material science Engineer Tomsk Polytechnic University; Buslovich specialist in material science assistant of Tomsk Polytechnic University; Nguyen Dyk An Vietnamese specialist in the field of materials science assistant of Tomsk Polytechnic University; Huang Qitao (2018)
Mechanical and tribotechnical characteristics of solid-lubricant and polymer-polymeric composites of UHMWPE were studied for the sake of design extrudable, wear-resistant, selflubricant polymer mixtures for Additive Manufacturing (AM). Tribotechnical properties of UHMWPE blends with the optimized content of solid lubricant fillers (polytetrafluoroethylene, calcium stearate, molybdenum disulphide, colloidal graphite, boron nitride) were studied under dry sliding friction at different velocities (V=0.3 and 0.5 m/s) and loads (P=60 and 140 N). Also, in order to increase strength and wear-resistance of UHMWPE composites they were reinforced with wollastonite microfibers and aluminum metahydroxide AlO (OH) microparticles preliminary treated (functionalized) in polyorganosiloxane. The comparison on measured mechanical and tribotechnical properties are given with interpretation of the mechanisms of observed phenomenon.